Türk hukukunda gemi ipoteğinin kapsamı - Akdoğan, N. Elif (My University, 2004)
TÜRK HUKUKUNDA GEMİ İPOTEĞİNİN KAPSAMI Günümüzde, yeni bir geminin inşa edilmesi veya satın alınması amacı ile kredi almak yaygın olarak kullanılmaktadır. Kredi mukabilinde gemi üzerinde ipotek tesis edilmek suretiyle, büyük miktarlarda kredi temin eden kuruluş lehine bir hukuki güvence sağlanmaktadır. Zira, ipoteğin kapsamına giren unsurlardan biri olan gemi çok büyük bir iktisadi değeri temsil etmektedir. Bugün, gemi ipoteği, teminat fonksiyonunun yanı sıra uluslararası gemi finansmanında sık kullanılan bir finansman vasıtası özelliğini de haizdir. Kredi veren kuruluş tarafından mutlak surette talep edilen bir ayni teminat olan gemi ipoteği, tescil edileceği ülkenin hukukuna göre alacaklı için sağlam bir teminat teşkil etmemekte ise kredi bulmak imkansız hale gelebilecektir. Bu itibarla, ipoteğin “kapsamı” dahi ipotekli alacaklının dikkat ettiği hususlardan birini teşkil eder. Türk Hukukuna göre gemi ipoteği, sicile kayıtlı bir gemi, mahsus sicile kayıtlı inşa halindeki bir gemi veya böyle gemiler üzerindeki paylar üzerinde tesis olunabilir (TTK.md.875, 877, 897, 941). Çalışmamızın konusu, Türk Hukukunda sicile kayıtlı gemiler üzerinde tesis olunan bir akdi rehin nevi olarak akdi gemi ipoteğinin (TTK.md.875) kapsamıdır. İnşa halindeki gemiler üzerinde de tesis edilebilen akdi ipotek (diğer bir ifade ile yapı ipoteği) (TTK.md.941-944) ve bir kanuni rehin nevi olan kanuni gemi ipoteği (TTK.md.877) incelememizin sınırlarına dahil bulunmamaktadır. Gemi ipoteğinin kapsamının sağlam kanuni esaslara bağlanması ipoteğin sağlam ve emin bir teminat haline getirilmesi için, dolayısıyla ipotekli alacaklının himaye edilmesi bakımından büyük önem taşımaktadır. Bu çalışma ile Türk Hukukunda gemi ipoteğinin “kapsam”ına dair mevcut kanuni düzenlemedeki eksiklikler ve tasrih edilmesi gereken hususlar tespit ve izah edilmiştir. THE EXTENT OF SHIP MORTGAGE IN TURKISH LAW Nowadays, it is frequently being used to seek for loans to build or purchase a new vessel. Legal undertakings, or in other words, legal securities - are rendered for the account of institutions granting loans of considerable amounts for such transactions by placing mortgage on the vessels against the loan granted. This is for the reason that the vessel being the subject of the mortgage represents a considerably high economical value. Today, ship mortgage, besides having security function, is also a financial instrument used frequently in international ship financing. In the event that the ship mortgage conclusively requested by the loan granting institution as a collateral security does not constitute a solid security in the legislation of the state the vessel mortgage be registered for the beneficiary, it becomes impossible to find such finance. For this respect, the “extent of the ship mortgage” becomes one of the important features of the transaction which is considered by the beneficiary of the mortgage. According to Turkish Law, ship mortgage is permitted to be placed on the ships registered in the register of ship, the ship under construction registered to special registry or on the shares of such ships (T.C.C. Articles 875, 877, 897, 941). The scope of this work is the extent of contractual ship mortgage as being a contractual pledge instrument placed on the ships registered to register of ship in Turkish Law (T.C.C. Art. 875). The contractual mortgage be placed on the ships under construction (also known as construction mortgage) (T.C.C. Art. 941 – 944) and legal ship mortgage as of being a kind of legal pledge instrument (T.C.C. Art. 877) shall not be within the scope of this work. It is vital the extent of the ship mortgage to be based upon solid legal regulations in order to contruct the ship mortgage as a solid/ first class security and to protect the beneficiary of the mortgage. In this work, it has been established to bring the deficiencies and the provisions, which should be re-established relating to the extent of ship mortgage in current Turkish Law.
Keywords: İpotekler